2015
DOI: 10.1111/echo.12800
|View full text |Cite
|
Sign up to set email alerts
|

Value of Resting Echocardiographic Findings and Dobutamine Stress Echocardiography for Diagnosing Myocardial Ischemia in Patients with Suspected Angina Pectoris

Abstract: Integration of DSE and resting echocardiographic findings describing degree of heart calcification, impaired LAD flow, and extent of delayed ejection motion of the myocardium improves detection of coronary angiogram-based FFR-guided ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Whatever be the background etiology of chest pain, noninvasive imaging particularly DSE would continue to remain valuable in the clinical decision making process. The data published by Utsunomiya et al . in this issue of the Journal are just a confirmation of the need of compulsory continuation of research in DSE for further refinement of this cheap, noninvasive, safe, and bedside echocardiographic technique, available almost in every corner of the earth.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Whatever be the background etiology of chest pain, noninvasive imaging particularly DSE would continue to remain valuable in the clinical decision making process. The data published by Utsunomiya et al . in this issue of the Journal are just a confirmation of the need of compulsory continuation of research in DSE for further refinement of this cheap, noninvasive, safe, and bedside echocardiographic technique, available almost in every corner of the earth.…”
mentioning
confidence: 77%
“…So what is the relevance of the total heart calcification (THC) score and what is the relationship between total heart calcification score and functionally and hemodynamically significant coronary artery disease? As Utsunomiya et al have shown in Table III of their article, a THC score of >2 performed equally well as an LAD‐DSVR of <1.5 . Although they have not performed a specific correlation test to show the association between these two variables, there is a rather strong, although not universally proven, association between aortic stenosis and coronary atherosclerosis, both presumably having an underlying common inflammatory process, as has been highlighted in a review by Hermans, et al …”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Global and regional systolic myocardial deformation abnormalities at rest and during dobutamine stress in patients with CAD have been demonstrated in previous studies . Our study results indicate that GLS had a better predictive value than other diastolic and systolic strains and SR parameters or visual assessment.…”
Section: Discussionmentioning
confidence: 99%
“…We found that early longitudinal, circumferential, and radial diastolic SR had a tendency to be lower in patients with significant coronary stenosis even at rest; however, according to our results, they were not sensitive and specific enough to detect significant coronary artery stenosis even at peak doses (the greatest predictive value was of late radial diastolic SR at the low dobutamine dose (AUC 0.789 with 66.7% sensitivity and 91.7% specificity). Previous small clinical studies have demonstrated ischemia‐related diastolic abnormalities using tissue Doppler–derived strain echocardiography in CAD at rest . The study by Liang et al .…”
Section: Discussionmentioning
confidence: 99%